Os novos desafios do educador frente ao processo de globalização: A atuação do pedagogo no ambiente organizacional - Paes, Marcela Soares Polato; Adam, Joyce Mary [UNESP] (My University, 2015)
This study analyzed the role of the pedagogue in the non-formal education, especially in business context, to understand, through the development of a bibliographic research, considering theoretical references that discuss the thematic of this research and conducting a semi-structured interview with a professional who works in this area, the possibilities to promote a critical education committed with the formation needs of those involved, because the corporate education model has been disseminated in the current society and consolidated as a space for formation, pointing new spaces of action for the Pedagogue in contemporary.
The new challenges of the educator front of the globalization process: The role of the teacher in the organizational environment
Keywords: Education; Lesson plan; Planning